Bryophyte literature records database of Aysén, Chilean sub-Antarctic ecoregion - L. Sánchez-Jardón; A. Hernández de Diego; R. Mackenzie; M. Villodre; C. Arnaiz-Schmitz; M. F. Schmitz; B. Acosta-Gallo (Scientific Data)
Abstract The Chilean sub-Antarctic ecoregion hosts the largest expanse of temperate forests, wetlands and peatlands, as well as the largest proportion of protected areas in the southern hemisphere. Bryophytes are highly diverse and ecologically essential in sub-Antarctic ecosystems and are considered as biodiversity loss indicators caused by the current socio-ecological crisis. However, knowledge about their biodiversity is rather limited. Integrating the available information on bryophyte diversity in regional platforms such as SIB-Aysén can be useful to acknowledge their ecological importance and remarkable biodiversity. This article integrates 345 records of 273 bryophyte taxa known in the region of Aysén and emphasizes the need to include citizen science as a tool to increase observations in lesser-known taxonomic groups.